¿Estrategia reductiva? de la ecología de sistemas a la fisiología - Di Pasquo, Federico Martín (2017)
The main objective of this work is to analyze the intention to reduce some areas of Ecology (in particular Population Ecology, Community Ecology and Ecosistem Ecology) to Physiology (in the particular case of metabolic studies). The origin of this research of reduction was done through consolidation of metabolic ecological theory in first years of XXIst century. Considering this objective, general framework was based on the proposal of Sahotra Sarkar.